2013
DOI: 10.1371/journal.pone.0072406
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Strength of the Association and Agreement Levels between Subjective and Objective Sleep Duration in Adolescents

Abstract: Study ObjectivesThe majority of adolescent sleep research has utilized self-reported sleep duration and some have based information on a solitary question. Whilst some have claimed to have validated sleep survey data with objective actigraphy measures in adolescents, the statistical approach applied only demonstrates the strength of the association between subjective and objective sleep duration data and does not reflect if these different methods actually agree.MethodsData were collected as part of the Midlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 22 publications
7
106
2
9
Order By: Relevance
“…It is important to note that studies comparing selfreported sleep duration with objectively measured sleep amounts (ie, with actigraphy) suggest that self-reports of sleep often overestimate actual sleep duration, signifying that the problem of chronic sleep loss in adolescents may be even greater than the data indicate. 12 US-based 4,13 and international studies 5,6,14 revealed that as students get older, sleep durations decline. The National Sleep Foundation Sleep in America Poll 4 found that by the 12th grade, 75% of students self-reported sleep durations of less than 8 hours of sleep per night compared with 16% of sixth graders.…”
Section: Epidemiologic Studies Of Sleeping Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that studies comparing selfreported sleep duration with objectively measured sleep amounts (ie, with actigraphy) suggest that self-reports of sleep often overestimate actual sleep duration, signifying that the problem of chronic sleep loss in adolescents may be even greater than the data indicate. 12 US-based 4,13 and international studies 5,6,14 revealed that as students get older, sleep durations decline. The National Sleep Foundation Sleep in America Poll 4 found that by the 12th grade, 75% of students self-reported sleep durations of less than 8 hours of sleep per night compared with 16% of sixth graders.…”
Section: Epidemiologic Studies Of Sleeping Adolescentsmentioning
confidence: 99%
“…25 However, higher socioeconomic status is not necessarily protective because studies have also shown that youth from households with higher socioeconomic status have shorter sleep durations. 16,26 For older adolescents, additional environmental factors, such as after-school employment, 16 striving for good grades, 5,6,12 socializing, 27,28 participation in sports and other extracurricular activities, and lack of parental monitoring or rules about bedtimes, can further interfere with sleep durations. 6,29,30 School start times are reviewed later in the present report.…”
Section: Epidemiologic Studies Of Sleeping Adolescentsmentioning
confidence: 99%
“…Average weekday sleep duration was then calculated by adding sleep duration from Sunday through to Thursday and dividing by 5. 13 Similarly, average weekend sleep duration was derived in the same manner by adding sleep duration for Friday and Saturday and dividing by 2. 13 We then derived weekday sleep debt (average weekend sleep duration minus average weekday sleep duration).…”
Section: Sleep Measuresmentioning
confidence: 99%
“…13 Similarly, average weekend sleep duration was derived in the same manner by adding sleep duration for Friday and Saturday and dividing by 2. 13 We then derived weekday sleep debt (average weekend sleep duration minus average weekday sleep duration). Participants were also asked to complete 7-day sleep diaries at 6 and 12 months post-intervention.…”
Section: Sleep Measuresmentioning
confidence: 99%
“…Adolescents' estimates of sleep duration are strongly correlated with objective measurement in weekday sleep reports, and only moderately correlated in weekend sleep reports [15,16]. Selfreport validity may be significantly enhanced by daily diary entries [20].…”
Section: Introductionmentioning
confidence: 99%